Os danos ao projeto de vida como lesão a direitos da personalidade : viabilidade de reconhecimento no cenário jurídico brasileiro - Ferrari, Graziela Maria Rigo (2016)
This dissertation aims at analysing the viability of the recognition of a new concept related to the damage to the person, entitled “damage to the life project”, whose initial contribution is attributed to the Peruvian jurist Carlos Fernandez Sessarego. Therefore, it is presented the philosophical thought, based on the humanist and existentialist approaches, of the this concept, as well as it explores this concept in a political and legal context from the recognition of human rights, which, later, became fundamental rights. Besides, on the one hand, it shows the significant changes observed in the context of the personality rights, whether in the world scenario, either at the national level. On the other hand, it presents the origins, the concept and the scope of the “damage to the life project” and it analyses some decisions of the InterAmerican Court of Human Rights, a pioneer in deliberations relate to the “damage to the life project”. Finally, it discusses the first manifestations, in the national legal scenario, on such “damage”, showing the viability of its acceptance and the repair forms according to the critical analysis of jurisprudence.